Fitness profiles of elite male Italian teams handball players - Ruscello, B.; Castagna, C.; Carbonaro, R.; Gabrielli, P. R.; D'Ottavio, S. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this study was to examine the fitness profile of the Italian national male Team-Handball players of different competitive level. METHODS: Forty-one male handball players from the senior (N.=21, height 1.90±0.06m, body mass 94.04±11.59kg, BMI 26.13±2.45) to the junior category (N.=20, height 1.86±0.06m, body weight 84.99±12.52kg, BMI: 24.56±3.35) Italian National Teams participated in this study. Players were tested for lower and upper limbs muscle strength, change of direction ability and specific endurance. Lower limbs explosive strength was assessed with squat (SJ) countermovement (CMJ), stiff leg (stiffness) jumps. Explosive strength was assessed by measuring kinematic aspects of squat and bench exercises. Change of direction ability was assessed with the 505 test. The Yo-Yo intermittent recovery test (YYIR1) was considered for specific endurance. RESULTS: Large and significant differences (d>1; partial Eta²2>0.14; P<0.01) between senior and junior national team players were found in anthropometrics, jumping, power, sprint, agility, and aerobic fitness (junior body weight accounting for 10% less than the senior one, P=0.021; SJ and CMJ in juniors smaller than the seniors by 15% and 12%, P=0.000 and P=0.001, respectively). Similar differences were found among positional roles (goalkeepers, backs, centers, pivots, wings), suggesting practical implications for training. CONCLUSIONS: The differences between the competitive level and the playing role in relevant handball performance were reported in Italian national team players. The magnitude of the differences suggests the need of individual training approach when dealing with the young handball players.